The olfactory epithelium as a port of entry in neonatal neurolisteriosis. Issue 1 (December 2018) - Pägelow, Dennis; Chhatbar, Chintan; Beineke, Andreas; Liu, Xiaokun; Nerlich, Andreas; Vorst, Kira; Rohde, Manfred; Kalinke, Ulrich; Förster, Reinhold; Halle, Stephan; Valentin-Weigand, Peter; Hornef, Mathias; et al.
Abstract Bacterial infections of the central nervous system (CNS) remain a major cause of mortality in the neonatal population. Commonly used parenteral infection models, however, do not reflect the early course of the disease leaving this critical step of the pathogenesis largely unexplored. Here, we analyzed nasal exposure of 1-day-old newborn mice toListeria monocytogenes (Lm ). We found that nasal, but not intragastric administration, led to early CNS infection in neonate mice. In particular, upon bacterial invasion of the olfactory epithelium, Lm subsequently spread along the sensory neurons entering the brain tissue at the cribriform plate and causing a significant influx of monocytes and neutrophils. CNS infection required listeriolysin for penetration of the olfactory epithelium and ActA, a mediator of intracellular mobility, for translocation into the brain tissue. Taken together, we propose an alternative port of entry and route of infection for neonatal neurolisteriosis and present a novel infection model to mimic the clinical features of late-onset disease in human neonates. Listeria monocytogenes causes meningitis in newborns. Here, Pägelow et al. present a mouse model of neonatal cerebral listeriosis, and show that nasal inoculation, but not intragastric administration, leads to early brain infection in the absence of bacteraemia during the neonatal period.